COMMUNITY PARTICIPATION IN EMERGENCY WASTE MANAGEMENT: BETWEEN SOCIAL MOVEMENTS AND COMMUNITY INDEPENDENCE - Badruddin, Syamsiah; Halim, Paisal; P, Suci Ayu Kurniah (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The waste emergency in Indonesia is not only a technical issue, but also a social problem closely related to community participation patterns. This study aims to analyze how communities engage in waste management efforts through two main approaches: environmentally based social movements and strengthening community independence. A qualitative approach was used with case studies in three urban areas: Jakarta, Makassar, and Yogyakarta. Data were collected through in-depth interviews, participant observation, and community documentation. The research results show that community participation grows through a combination of ecological awareness, social mobilization, and local leadership. Social movements are able to raise collective spirit, while community independence determines the sustainability of the program. Success factors include the presence of driving figures, networks between residents, and local policy support. This research confirms that synergy between social movements and strengthening community independence is an important foundation in responding to the waste emergency in an inclusive and sustainable manner.